Clinical Observation of a Child with KID (Keratitis-Ichthyosis-Deafness) Syndrome - V.A. Klymenko; O.P. Zdybska; T.V. Sirenko; O.M. Plakhotna; N.R. Viun (Zaslavsky O.Yu., 2015)
A clinical case of keratitis-ichthyosis-deafness (KID syndrome) in an infant is described. The article familia-rizes pediatricians and family doctors with difficulties in the diagnosis of this rare genetic disease in infants.